Utilization of Digital Marketing on the Development of Micro, Small and Medium Enterprises (MSMEs) in Jebres District, Surakarta City - Sri Wijiastuti; Kurniawati Darmaningrum (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
The aims of this study are: (1) To partially analyze the effect of knowledge, use, and type of internet media on the business performance of the Creative Sector MSMEs in Jebres District, Surakarta City. (2) To partially determine the effect of digital marketing mediation on the influence of knowledge, use, and type of internet media on Creative Sector SMEs in Jebres District. This research was conducted on MSMEs in Jebres District, Surakarta City. The population in this study of MSMEs in the creative sector (handicrafts, fashion, culinary) is unknown. Therefore the determination of the number of samples using the Slovin formula obtained a sample of 100 respondents. The purposive sampling technique did sampling in this study. The study results concluded that, partially, there was a positive and significant influence on the knowledge, use, and type of internet media variables on the business performance of the Creative Sector MSMEs in Jebres District, Surakarta City. It is known that there is a complete mediation effect of digital marketing on the influence of knowledge, use, and type of internet media on MSME business performance.